Potensi Interaksi Obat di Sistem Pencernaan pada Resep Apotek Kota Bandung, November 2023 - Shafira Galuh Peratiwi; Raden Maya Febriyanti (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Medications used for gastrointestinal (GI) disease therapy are widely prescribed or over-the-counter, ranking among the top 10 prescribed and sold globally. These drugs are often concurrently used with other medications, leading to potential drug interactions that can impact their effectiveness. However, the identification of potential interaction severity remains limited. This study focuses on identifying drug interactions in patients with digestive disorders through common prescriptions in Bandung city in November 2023. Out of 50 analyzed prescriptions, 20 potential drug interactions were identified, comprising 8 minor and 12 moderate interactions, with no major interactions. The findings underscore the pharmacist's crucial role in counseling and providing drug information to enhance therapy effectiveness and patients' quality of life.